Mewujudkan Nilai-Nilai Kemanusiaan dengan Bakti Sosial - Rahayu Mardikaningsih; Eli Retnowati; Eli Masnawati; Siti Nur Halizah; Didit Darmawan; Arif Rachman Putra; Misbachul Munir; Rafadi Khan Khayru; Rommy Hardyansah (Forum Kerjasama Pendidikan Tinggi, 2024)
Community service activities (PkM) in the form of social service (baksos) through the distribution of basic food packages are a positive step to provide assistance to people in need. The distribution of food packages is not only material in nature, but also reflects significant social care and solidarity. The purpose of this PkM is to provide assistance in the form of food packages to residents around Sunan Giri University Surabaya (UNSURI). This activity involves students and lecturers to distribute food packages to residents around the campus. The stages of community service consist of methods of collecting basic necessities, targeting basic necessities, basic necessities received, methods of implementing the distribution of basic necessities. The result of this activity is the assistance provided to residents in need. Although the amount of assistance is not large, this social service has succeeded in lightening the burden on the community. This Community Service (PkM) activity has a positive impact on all parties involved, as reflected in the positive response of the community. In addition, this social service activity also provides opportunities for students to develop life skills such as empathy and concern for others.